PREMENSTRUAL SYNDROME FREQUENCY, PREMENSTRUAL SYNDROME COPING STRATEGIES AND FACTORS AFFECTING PREMENSTRUAL SYNDROME IN UNIVERSITY STUDENTS IN TURKEY - Özmermer, Tuğba; Koruk, Fatma (LIFE: International Journal of Health and Life-Sciences, 2019)
Premenstrual syndrome (PMS) symptoms influence women’s lives to a large extent. This study was conducted to understand the frequency of PMS, coping strategies and factors affecting PMS in university students in Sanliurfa, Turkey. In this cross-sectional study in which 376 university students were reached. 52.1% of the students were found to experience PMS. Engaging in various activities to expend energy eating sweets and using analgesics were found to be the most common methods used by the students to cope with PMS symptoms; however, they were not able to cope efficiently with water retention, balance/control issues and autonomic reactions. The logistic regression analysis showed that a unit of increase in age led PMS risk to increase by a factor of 1.179, whereas a unit of increase in weight led to an increase in PMS risk by a factor of 1.025. Also, low income increased PMS risk by a factor of 1.884, fast food consumption increased it by a factor of 2.069, high salt consumption by a factor of 1.884, and anemia presence by a factor of 1.739. In conclusion, the prevalence of PMS was found to be high in the students and they were observed to have difficulty in coping with certain symptoms. On the basis of the results of the study, it is recommended that university students be given information about factors affecting PMS, how to cope with symptoms, what treatments are available, and that they been couraged to receive treatment for PMS.